Dialectic Of Tasyri' and Sharia Philosophy: Affirming The Relevance Of Islamic Law Values In The Direction Of Islamic Law Reform In Indonesia - yusuf, nasruddin; Willya , Evra; Ibrahim, Fathum; Yusuf, Aisyiyah Mumtazah N. (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
This study offers a novel contribution by examining the integration of Tasyri’ and Sharia philosophy within the framework of Islamic law reform in Indonesia. The originality of this research lies in its emphasis on how philosophical integration can reinforce the foundations of contemporary Islamic legislation in a pluralistic context. The primary focus is to explore how the fundamental values of Islamic law can be effectively applied within a modern legislative system that responds to the nation’s social dynamics and constitutional demands. This integration is crucial for bridging the principles of tasyri’—as the normative basis for legal formation—with sharia as a comprehensive legal system that governs human life. This study employs a normative qualitative method, analyzing primary legal sources, positive law, and contemporary literature, with a focus on maqasid al-shariah and comparative analysis across legal schools. The results demonstrate that integrating Tasyri’ and Sharia philosophy as both conceptual and normative foundations in Islamic law-making provides a comprehensive framework that bridges transcendent legal sources with the sociological realities of the ummah. This integration enables the application of Islamic law, which remains relevant to contemporary needs, while enriching national legislation with strong ethical and moral underpinnings. The main challenge lies in harmonizing classical texts with modern social realities to maintain the dynamism, adaptability, and contextual responsiveness of Islamic law. Therefore, the integration of Tasyri’ and Sharia philosophy is not merely theoretical but also practical, supporting the development of national legislation rooted in Islamic values and responsive to the complexity of Indonesia’s pluralistic society.